THE PLASTIC WASTE CRISIS IN INDONESIA AND THAILAND: CHALLENGES, ENVIRONMENTAL IMPACTS, AND SUSTAINABLE SOLUTIONS - Aulia Nurhanifah; Oot Hotimah; Elma Amalia Agustine; Bunga Febianto (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The plastic waste crisis in Indonesia and Thailand is one of the biggest environmentalchallenges in Southeast Asia, triggered by increased plastic consumption due to urbanization,economic growth and modern lifestyles. This study aims to analyze the challenges,environmental impacts, and sustainable solutions related to plastic waste management in bothcountries. The method used is qualitative analysis based on secondary data from scientificliterature, reports of international institutions. The results show that Indonesia faces seriousproblems in plastic waste management that cause marine pollution to other countries, whileThailand struggles with the high volume of domestic and imported plastic waste. Theresulting environmental impacts include damage to marine ecosystems, threats tobiodiversity, and human health risks from microplastics. Recommended solutions include theimplementation of national regulations that support sustainability principles, 3R (Reduce,Reuse, Recycle) strategies, promotion of eco-friendly packaging, and public education toreduce the use of single-use plastics. The study concludes that regional collaboration amongASEAN countries is needed to effectively address the plastic waste crisis to protectecosystems and human health in the long term.